Pro-Inflammatory Signaling by IL-10 and IL-22: Bad Habit Stirred Up by Interferons? - Mühl, Heiko (Frontiers in Immunology, 2013)
Interleukin (IL)-10 and IL-22 are key members of the IL-10 cytokine family that share characteristic properties such as defined structural features, usage of IL-10R2 as one receptor chain, and activation of signal transducer and activator of transcription (STAT)-3 as dominant signaling mode. IL-10, formerly known as cytokine synthesis inhibitory factor, is key to deactivation of monocytes/macrophages and dendritic cells. Accordingly, pre-clinical studies document its anti-inflammatory capacity. However, the outcome of clinical trials assessing the therapeutic potential of IL-10 in prototypic inflammatory disorders has been disappointing. In contrast to IL-10, IL-22 acts primarily on non-leukocytic cells, in particular epithelial cells of intestine, skin, liver, and lung. STAT3-driven proliferation, anti-apoptosis, and anti-microbial tissue protection is regarded a principal function of IL-22 at host/environment interfaces. In this hypothesis article, hidden/underappreciated pro-inflammatory characteristics of IL-10 and IL-22 are outlined and related to cellular priming by type I interferon. It is tempting to speculate that an inherent inflammatory potential of IL-10 and IL-22 confines their usage in tissue protective therapy and beyond that determines in some patients efficacy of type I interferon treatment.